2010
DOI: 10.1159/000278348
|View full text |Cite
|
Sign up to set email alerts
|

Lower Barthel Index Scores Predict Less Prescription of Pharmacological Therapy in Elderly Patients with Alzheimer Disease

Abstract: Aims: To determine the factors associated with receiving specific treatment (cholinesterase inhibitors or/and memantine) for Alzheimer disease (AD) in elderly patients. Methods: An observational study carried out in 289 consecutive outpatients aged >64 years with dementia. We collected data on specific AD therapy, sociodemographic variables, Barthel Index (BI), Lawton and Brody Index (LI), Mini Mental State Examination, Global Deterioration Scale (GDS), Charlson Index and the total number of drugs chronically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 54 publications
(29 reference statements)
1
7
0
Order By: Relevance
“…cholinesterase inhibitors, memantine and/or Ginkgo biloba ). While odds ratios for Alzheimer's disease are presumably higher than those for vascular dementia, it is in accordance with the results of Formiga and Frisoni [36,40]. Moreover, there are several hints of different prescribing patterns of neurologists and GPs [25,38].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…cholinesterase inhibitors, memantine and/or Ginkgo biloba ). While odds ratios for Alzheimer's disease are presumably higher than those for vascular dementia, it is in accordance with the results of Formiga and Frisoni [36,40]. Moreover, there are several hints of different prescribing patterns of neurologists and GPs [25,38].…”
Section: Discussionsupporting
confidence: 86%
“…According to Formiga, lower Barthel Index scores predict fewer prescriptions of pharmcological therapy in Alzheimer's disease [40]. Other factors like patient age, gender, co-morbidity, neuroleptic and antidepressant therapy, and hospital admission in the previous year show no significance after adjusting the multivariate logistic regression model.…”
Section: Discussionmentioning
confidence: 99%
“…It is scored on a scale of 1 to 7 (0, no cognitive decline; 2, very mild cognitive decline; 3, mild cognitive decline; 4, moderate cognitive decline; 5, moderately severe cognitive decline; 6, severe cognitive decline; and 7, very severe cognitive decline). [3739] The validity of the Korean version of the GDS has been demonstrated. [23]…”
Section: Methods and Designmentioning
confidence: 99%
“…Dependence has also been related to ND: Formiga et al [ 44 ] found that only 15.3% of patients with AD were independent, in addition to an association between severe dementia and low scores on the Barthel Index. Aside from the cultural role of older adults with ND, and the lack of social occupation, general motor system dysfunction has been shown in AD, which could be relevant to the appearance of contractures, followed by immobility, and decreased muscular tone[ 45 ].…”
Section: Discussionmentioning
confidence: 99%